2018
DOI: 10.1038/s41598-018-19761-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy drugs cyclophosphamide, cisplatin and doxorubicin induce germ cell loss in an in vitro model of the prepubertal testis

Abstract: Long term survival rates for childhood cancers is steadily increasing, however cancer survivors can experience fertility problems as a consequence of chemotherapy treatment. This is particularly problematic for young boys, for whom no fertility preservation treatment is yet established. Here, we have determined the effects on prepubertal mouse testis of three commonly used chemotherapy drugs; cyclophosphamide (using its active metabolite phosphoramide mustard), cisplatin and doxorubicin, exposing testicular fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 50 publications
(72 reference statements)
3
59
1
Order By: Relevance
“…No change in Leydig cells function and morphology has been observed in the pre-pubertal testis after 48 h in vitro exposure to doxorubicin [31]. Similarly, recent data have reported that Leydig cell density was unaffected after 24 h in vitro exposure to cisplatin, cyclophosphamide, and doxorubicin [24]. Although no change has been observed in rodent Leydig cells in in vitro studies, elevated LH levels found in survivors of paediatric cancer might suggest Leydig cell alteration; the few studies available do not currently allow conclusions to be drawn about the impact of chemotherapy exposure during childhood on testicular somatic cells.…”
Section: Effects Of Chemotherapy On Somatic Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…No change in Leydig cells function and morphology has been observed in the pre-pubertal testis after 48 h in vitro exposure to doxorubicin [31]. Similarly, recent data have reported that Leydig cell density was unaffected after 24 h in vitro exposure to cisplatin, cyclophosphamide, and doxorubicin [24]. Although no change has been observed in rodent Leydig cells in in vitro studies, elevated LH levels found in survivors of paediatric cancer might suggest Leydig cell alteration; the few studies available do not currently allow conclusions to be drawn about the impact of chemotherapy exposure during childhood on testicular somatic cells.…”
Section: Effects Of Chemotherapy On Somatic Cellsmentioning
confidence: 81%
“…However, in contrast to germ cells, Sertoli cells seemed to develop a better resistance to chemotherapeutic agents in an animal model. In vitro studies using prepubertal rat testis showed no impact on the Sertoli cell number after 48 h exposure to doxorubicin, cisplatin, or cyclophosphamide [24]. Another study highlighted cell death resistance in primary Sertoli cells isolated from prepubertal rat, after 24 h in vitro exposure to cisplatin and etoposide.…”
Section: Effects Of Chemotherapy On Somatic Cellsmentioning
confidence: 99%
“…For each analysis of every experimental treatment, all technical replicates from one patient were combined to give a single datapoint. Tissues were exposed to chemotherapy drugs for a short time period, as in previous work by us and others, to mimic the short period of exposure that patients usually experience each drug cycle (Morgan et al 2013, Lopes et al 2014, Lande et al 2017, Rossi et al 2017, Smart et al 2018. On Day 3 of culture, after 24 h of drug exposure, tissue from experimental treatments was moved to drug-free medium for 96 h, with medium changed after 48 h: Control tissue was kept in drug-free medium throughout, with medium changed at the same time as for experimental groups.…”
Section: Human Ovary Tissue Culturementioning
confidence: 99%
“…Consequently most prepubertal male patients who receive cancer treatment will achieve normal pubertal development . Further research continues to try and establish the mechanisms by which different treatments lead to damage …”
Section: Cancer and Fertilitymentioning
confidence: 99%
“…52,54,55 Further research continues to try and establish the mechanisms by which different treatments lead to damage. 56,57 Green et al, report that when compared with their siblings, survivors of childhood cancer were approximately half as likely to sire a pregnancy. 58 It remains unclear at present whether there is a longterm generational impact on the fertility of children born from male cancer survivors with a Danish study reporting no significant association 59 but potential mechanisms of effect have been identified in animal work.…”
Section: Disruption Of Hypothalamicpituitary-gonadal Axismentioning
confidence: 99%